Analysis of the Vacuum-Steam Defrosting Process of Plums Pre-Treated with Dehydrofreezing (Agricultural Engineering, 2020)
The research material was prune plums (Prunus domestica L.), subjected to osmotic pre-treatment, with variable process time parameters and osmotic solution concentration. Plums thus fixed were frozen and stored for 6 months. At even (monthly) intervals, the product was defrosted by the vacuum-steam method, using the s-p-p chamber, until the thermocouple indicated a temperature of 4ºC in the sample’s thermal center. In order to study the kinetics of phenomena occurring during the defrosting process, the chamber was equipped with a measuring system to enable measurement and recording of temperature changes in time in the geometric center of the sample, as well as the temperature on the sample surface. The conducted tests proved that the time of vacuum-steam defrosting of fruit depended on the amount of water contained in it. In plums dehydrated in 45-65% sucrose solutions, duration of the defrosting process was shortened already after three months of frozen storage. After 6 months of storage, defrosting of these fruits was twice as fast as that of control samples.